Roles of proteolysis in regulation of GPCR function. (16th January 2013) - Cottrell, GS
<x xml:space="preserve">Abstract</x> The enzymatic activity of peptidases must be tightly regulated to prevent uncontrolled hydrolysis of peptide bonds, which could have devastating effects on biological systems. Peptidases are often generated as inactive propeptidases, secreted with endogenous inhibitors, or they are compartmentalized. Propeptidases become active after proteolytic removal of N‐terminal activation peptides by other peptidases. Some peptidases only become active towards substrates only at certain pHs, thus confining activity to specific compartments or conditions. This review discusses the different roles proteolysis plays in regulating GPCRs. At the cell‐surface, certain GPCRs are regulated by the hydrolytic inactivation of bioactive peptides by membrane‐anchored peptidases, which prevent signalling. Conversely, cell‐surface peptidases can also generate bioactive peptides, which directly activate GPCRs. Alternatively, cell‐surface peptidases activated by GPCRs, can generate bioactive peptides to cause transactivation of receptor tyrosine kinases, thereby promoting signalling. Certain peptidases can signal directly to cells, by cleaving GPCR to initiate intracellular signalling cascades. Intracellular peptidases also regulate GPCRs; lysosomal peptidases destroy GPCRs in lysosomes to permanently terminate signalling and mediate down‐regulation; endosomal peptidases cleave internalized peptide agonists to regulate GPCR recycling, resensitization and signalling; and soluble intracellular peptidases also participate in GPCR function by regulating the ubiquitination state of GPCRs, thereby altering GPCR signalling and fate. Although the use of peptidase inhibitors has already brought success in the treatment of diseases such as hypertension, the discovery of new regulatory mechanisms involving proteolysis that control GPCRs may provide additional targets to modulate dysregulated GPCR signalling in disease.